Exceedingly low genetic diversity in snow leopards due to persistently small population size - Katherine A. Solari; Simon Morgan; Andrey D. Poyarkov; Byron Weckworth; Gustaf Samelius; Koustubh Sharma; Stephane Ostrowski; Uma Ramakrishnan; Zairbek Kubanychbekov; Shannon Kachel; Örjan Johansson; Purevjav Lkhagvajav; et al. (Proceedings of the National Academy of Sciences, 2025)
Snow leopards ( Panthera uncia ) serve as an umbrella species whose conservation benefits their high-elevation Asian habitat. Their numbers are believed to be in decline due to numerous anthropogenic threats; however, their conservation is hindered by numerous knowledge gaps. In particular, the dearth of genetic data, unique among all big cat species, hinders a full understanding of their population structure, historical population size, and current levels of genetic diversity. Here, we use whole-genome sequencing data for 41 snow leopards (37 newly sequenced) to offer insights into these unresolved aspects of snow leopard biology. Among our samples, we find evidence of a primary genetic divide between the northern and southern part of the range around the Dzungarian Basin—as previously identified using landscape models and fecal microsatellite markers—and a secondary divide south of Kyrgyzstan around the Taklamakan Desert. Most noteworthy, we find that snow leopards have the lowest genetic diversity of any big cat species, likely due to a persistently small population size throughout their evolutionary history rather than recent inbreeding. We also find that snow leopards have significantly less highly deleterious homozygous load compared to numerous Panthera species, suggesting effective purging during their evolutionary history at small population sizes. Without a large population size or ample standing genetic variation to help buffer them from any forthcoming anthropogenic challenges, snow leopard persistence may be more tenuous than currently appreciated.